Types of Teachers in the Context of Geographical Key Concepts. Reconstructing Professional Beliefs of Geography Teachers - Fögele, Janis (Journal of Geography Education, 2018)
Key concepts as the big ideas of a subject are a means to support learners to think geographically. Thus, they are a means to cope with complex issues geographically. Therefore, teachers must be able to design geography lessons based on key concepts. Key concepts are at the core of a long-term in-service teacher training. This study examines the teachers’ professional beliefs concerning geographical key concepts, as these implicit orientations are central for the implementation of innovations. Using the documentary method these beliefs were reconstructed, leading to four types of teachers that differ on different usages of geographical key concepts.